Springer Handbook of Ocean Engineering - Dhanak, Manhar R.; Xiros, Nikolaos I. (Springer Handbooks, 2016)
The handbook is the definitive reference for the interdisciplinary field that is ocean engineering. It integrates the coverage of fundamental and applied material and encompasses a diverse spectrum of systems, concepts and operations in the maritime environment, as well as providing a comprehensive update on contemporary, leading-edge ocean technologies. Coverage includes but is not limited to; an overview of ocean science, ocean signals and instrumentation, coastal structures, developments in ocean energy technologies, and ocean vehicles and automation. The handbook will be of interest to practitioners in a range of offshore industries and naval establishments as well as academic researchers and graduate students in ocean, coastal, offshore, and marine engineering and naval architecture.